Ketahanan Papan Komposit dari Pelepah Sagu (Metroxylon sago Rottb.) terhadap Jamur Pelapuk dan Rayap Tanah - Deni Zulfiana; Sukma S. Kusumah (BRIN Publishing, 2014)
This study aimed to examine the resistance of composite boards made of sago frond using polyurethane (PU) and phenol formaldehyde (PF) adhesives against rotting fungi and termite. Dimension and targeted density of composite board were 30 cm × 30 cm × 1 cm and 0.5 g cm⁻³, respectively. Composite boards were prepared by cold press machine for composite boards using PU resin as a binder and hot press machine for boards using PF resin under the following conditions: 25 kg cm⁻² for 24 hours in cold pressing process and 10 minutes in hot pressing process with 140°C of temperature. Solid content of liquid adhesives was 50% with resin content as variations in this study i.e. 10%, 12% and 14%. The boards were tested against JIS K 1571 2004. The results show the composite boards treated with PU and PF adhesives were not resistant to rotting fungi and termites.